2022
DOI: 10.3389/fvets.2022.822032
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Tissue Distribution of Enrofloxacin Following Single Oral Administration in Yellow River Carp (Cyprinus carpio haematoperus)

Abstract: The pharmacokinetics and tissue distribution of enrofloxacin were determined in Yellow River carp (Cyprinus carpio haematopterus) reared at 20°C after single oral administration of enrofloxacin at 10 mg·kg−1 body weight (BW). Plasma, bile, and different tissue samples, including liver, kidney, gill, gut, and skin-muscle, were collected at predetermined times points. An HPLC method was developed to simultaneously determine the concentrations of enrofloxacin and its metabolite, ciprofloxacin. However, ciprofloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The terminal half-life (t 1/2λ ) was further estimated as ln (2)/λz (Yang et al, 2022). The area under the concentration versus time curve (AUC) and area under the first moment from 0 to infinity (AUMC 0-∞ ) were calculated using the linear trapezoidal method.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…The terminal half-life (t 1/2λ ) was further estimated as ln (2)/λz (Yang et al, 2022). The area under the concentration versus time curve (AUC) and area under the first moment from 0 to infinity (AUMC 0-∞ ) were calculated using the linear trapezoidal method.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…Especially in China, it has become one of the most commonly farmed fish species. Yellow River carp ( Cyprinus carpio Haematopterus ) is a valuable variety with the crucial economic value among different carp species ( 1 ). It mainly referred to the carp living in the Yellow River.…”
Section: Introductionmentioning
confidence: 99%
“…However, Trouchon and Lefebvre reported that both enrofloxacin and ciprofloxacin undergo intestinal recirculation via bile excretion [ 3 ]. In their recent report, Yang et al showed that in Yellow River carp, bile excretion might be the primary elimination route of enrofloxacin [ 33 ].…”
Section: Pharmacokinetics Of Enrofloxacinmentioning
confidence: 99%